Eksistensi Pendidikan Islam Dalam Bingkai Regulasi Pendidikan Di Indonesia Pasca Kemerdekaan - Harmonedi, Harmonedi; Zalnur, M (Belajea: Jurnal Pendidikan Islam, 2020)
Islamic education existed in Indonesia along with Islam comed. The existence of Islamic education has a long history along with the history of the life journey of the Indonesian people. Islamic education faces a variety of dynamics along with political dynamics. Through this research, it will be revealed how the existence of Islamic education in the framework of education regulation in Indonesia: problems, solutions and strategies in its development. This research uses descriptive method with a library research approach, which is research conducted by reading various papers related to the issues being studied. Based on the research, it is found that education regulations in post-independence Indonesia always accommodate Islamic education, because Muslims are the majority comunity in Indonesia. The government’s efforts to accommodate Islamic education were carried out gradually, and it was heavily influenced by political dynamics. This can be seen in several regulations issued by the government since the early independence period, orde baru, and pasca reformasi. The latest education regulations that accommodate Islamic education are Law Number 20 of 2003 about the National Education System and Law Number 18 of 2019 about pesantren. The existence of these two laws is an opportunity and at the same time a challenge for Islamic education, not only to overcome its own problems, but also to continue to develop itself and increase its role in nation building